2023
DOI: 10.1038/s41417-022-00578-8
|View full text |Cite
|
Sign up to set email alerts
|

NCBP2 and TFRC are novel prognostic biomarkers in oral squamous cell carcinoma

Abstract: There are few prognostic biomarkers and targeted therapeutics currently in use for the clinical management of oral squamous cell carcinoma (OSCC) and patient outcomes remain poor in this disease. A majority of mutations in OSCC are loss-of-function events in tumour suppressor genes that are refractory to conventional modes of targeting. Interestingly, the chromosomal segment 3q22-3q29 is amplified in many epithelial cancers, including OSCC. We hypothesized that some of the 468 genes located on 3q22-3q29 might … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In addition to investigating the clinicopathological variation across the different anatomical subsites, it was also prudent to investigate the oncogenes that drive carcinogenesis and have the potential to be employed as prognostic variables and therapeutic targets. Recent advances in high-throughput multi-omic technologies have enabled full molecular profiling of tumor samples to discover drivers of oncogenesis and progression, which may lead to the development of targeted oncotherapeutics which influence prognosis and survival of oral cancer at different anatomical subsites [ 30 ]. For example, NCBP2 and TFRC expression had been recently associated with increased mortality in patients with OSCC, with targeted NCBP2 depletion showing promising results as a novel oncotherapy for the suppression cell migration, invasion, and proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to investigating the clinicopathological variation across the different anatomical subsites, it was also prudent to investigate the oncogenes that drive carcinogenesis and have the potential to be employed as prognostic variables and therapeutic targets. Recent advances in high-throughput multi-omic technologies have enabled full molecular profiling of tumor samples to discover drivers of oncogenesis and progression, which may lead to the development of targeted oncotherapeutics which influence prognosis and survival of oral cancer at different anatomical subsites [ 30 ]. For example, NCBP2 and TFRC expression had been recently associated with increased mortality in patients with OSCC, with targeted NCBP2 depletion showing promising results as a novel oncotherapy for the suppression cell migration, invasion, and proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in high-throughput multi-omic technologies have enabled full molecular profiling of tumor samples to discover drivers of oncogenesis and progression, which may lead to the development of targeted oncotherapeutics which influence prognosis and survival of oral cancer at different anatomical subsites [ 30 ]. For example, NCBP2 and TFRC expression had been recently associated with increased mortality in patients with OSCC, with targeted NCBP2 depletion showing promising results as a novel oncotherapy for the suppression cell migration, invasion, and proliferation [ 30 ]. Furthermore, the recent identification of SERPINH1 as a protein with notable cell-surface expression in the oncogenesis of head-and-neck-SCCs has aided the development of a novel photothermal assisted targeted oncotherapy via gold nanostars combined with the searched SERPINH1 antibody; thereby illustrating the potential of key genes as biomarkers and therapeutic targets for OSCC [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a CBC, NCBP2 could recognize the m 7 G "cap" on RNA and promote RNA maturation, transportation, and translation in conjunction with eIF4E [18,[33][34][35][58][59][60][61][62]. Moreover, several studies have indicated that NCBP2 promotes the proliferation, metastasis, and immune escape of oral squamous cell carcinoma and head and neck squamous cell carcinoma [63,64]. Consistent with these findings, we identified that NCBP2 promotes PDAC progression by upregulating c-JUN-mediated MEK/ERK signaling activation in an m 7 G methylation-dependent manner.…”
Section: Discussionmentioning
confidence: 99%